Peran Otoritas Jasa Keuangan (OJK) dalam Meningkatkan Keuangan Inklusif melalui Akselerasi Pengembangan Pembiayaan UMKM - Layyinaturrobaniyah Layyinaturrobaniyah; Mutiara Syifa (Jurnal Intelek Insan Cendikia, 2026)
Financial inclusion plays a crucial role in driving the growth of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. The Financial Services Authority (OJK) has a strategic role in accelerating MSME financing access through policies such as People's Business Credit (KUR), technology-based crowdfunding services, and an inclusive financial ecosystem. This study analyzes the effectiveness of OJK’s role, regulatory alignment, and coordination with Bank Indonesia, the Ministry of Finance, and the Ministry of Cooperatives and SMEs. Using a descriptive qualitative method based on literature reviews and secondary data, the findings indicate that OJK has implemented various  strategic initiatives but still faces challenges in regulatory harmonization and inter-agency coordination. Therefore, stronger synergy among stakeholders is needed to create a more inclusive and sustainable MSME financing ecosystem.